The clinical evaluation of International Normalized Ratio variability and control in conventional oral anticoagulant administration by use of the variance growth rate. Issue 8 (14th August 2013) - Ibrahim, S.; Jespersen, J.; Poller, L.; ,
Summary Introduction The time in target International Normalized Ratio (INR) range (TIR) is used to assess the control and intensity of oral anticoagulation, but it does not measure variation in the INR. Objectives The value of assessing INR variability by use of the variance growth rate (VGR) as a predictor of events was investigated in patients treated with warfarin. Methods Three different methods of VGR determination (A, B1, and B2) together with the TIR were studied. Method A measures both INR variability and control, but methods B1 and B2 measure variability only. The VGR and TIR were determined over three time periods: overall follow‐up to an event, and 6 months and 3 months before an event. Results Six hundred and sixty‐one control patients were matched to 158 cases (bleeding, thromboembolism, or death). With all VGR methods, the risk of an event was greater in unstable patients at 6 months before an event than in stable patients. Method A demonstrated the greatest risk 3 months before an event in the unstable VGR group as compared with the stable group (odds ratio 3.3, 95% confidence interval 1.9–5.7, P < 0.005). The risk of an event was 1.9 times greater in patients with a low TIR (< 39%) than in those with a high TIR (> 80%) in the 3‐month period (P = 0.02). Risk of bleeding was significantly greater in the 3‐month period in patients with unstable VGR, with the greatest risk found with method B2 (P < 0.01). Conclusions Patients with unstable anticoagulation have a significantly increased risk of 'clinical events' at 3 and 6 months before an event. The VGR can be incorporated into computer‐dosage programs, and may offer additional safety when oral anticoagulation is monitored.